Composite particle

JP2024050748A5Inactive Publication Date: 2025-04-10SUMITOMO CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024014124
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2016-09-30
Filing Date
2024-02-01
Publication Date
2025-04-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing luminescent particles face issues with structural instability and low colloidal stability, particularly in aqueous environments, limiting their effectiveness as markers.

Method used

Combining a silica polymer with a light-emitting polymer containing pendant polar groups, and incorporating polyether groups on the particle surface to enhance colloidal stability, allowing for the formation of stable luminescent particles.

Benefits of technology

The resulting composite particles exhibit high structural stability and colloidal stability, enabling their use in various liquid environments, including aqueous buffers, with enhanced solubility and compatibility for biological applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000022_0000
    Figure 00000022_0000
  • Figure 00000022_0001
    Figure 00000022_0001
  • Figure 00000022_0002
    Figure 00000022_0002
Patent Text Reader

Abstract

To provide structurally stable light-emitting particles, light-emitting particles having high colloidal stability, and a simple synthesis method thereof.SOLUTION: Tetraalkoxysilane is hydrolyzed in the presence of an aqueous dispersion of a light-emitting polymer, which comprises a main chain and polar groups pendant from the main chain, so as to synthesize colloid or composite particles in which the light-emitting polymer and silane are combined.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to composite luminescent particles and their use as luminescent markers. The present invention relates to a method for preparing said composite particles. [Background technology]

[0002] Due to their hydrophilicity, silica nanoparticles can be dissolved in aqueous solvents, even at very high solids contents. , which form very stable suspensions in, for example, aqueous biological buffers. Silica and Luminescent Materials The nanoparticles are disclosed as labeling or detection reagents.

[0003] Nanoscale Res.Lett., 2011, vol.6, p.328, The entrapment of small molecules in a matrix is ​​disclosed.

[0004] Langmuir, 1992, vol. 8, pp 2921-2931, Silane Cup They disclose coupling of dyes to ring agents and subsequent incorporation into silica spheres. .

[0005] J.Mater.Chem.,2013,vol.1,pp3297-3304,Be Hrendt et al. developed silica-LEP nanoparticles in which LEP is covalently bonded to silica. The particles are described in which a light-emitting polymer reacts with a silica monomer during the formation of nanoparticles. It has alkoxysilane groups pendant from the polymer backbone.

[0006] Nanoscale,2013,vol.5,pp8593-8601,Geng e al. reported that LEPs have pendant non-polar alkyl side chains and that the nanoparticles are “SiO2@ Silica-conjugated polymer (CP) nanoparticles with a “CP@SiO2” structure are described.

[0007] Chem.Mater.,2014,vol.26,pp1874-1880,Gen G et al. reported poly(9,9-dihexylfluorene-alt-2,1,3-benzo[a]phenyl]fluorene. The present invention discloses nanoparticles loaded with fluorophore (PFBT). [Prior art documents] [Non-patent literature]

[0008] [Non-Patent Document 1] Nanoscale Res.Lett.,2011,vol.6,p328 [Non-Patent Document 2] Langmuir,1992,vol.8,pp2921-2931 [Non-Patent Document 3] J.Mater.Chem.,2013,vol.1,pp3297-3304,Behrendt et al. [Non-Patent Document 4] Nanoscale,2013,vol.5,pp8593-8601,Geng et al. [Non-Patent Document 5] Chem.Mater.,2014,vol.26,pp1874-1880,Geng et al. Summary of the Invention [Problem to be solved by the invention]

[0009] It is an object of the present invention to provide luminescent particles which are structurally stable.

[0010] It is still a further object of the present invention to provide luminescent particles having high colloidal stability. be.

[0011] It is still a further object of the present invention to provide a simple synthesis of said luminescent particles. [Means for solving the problem]

[0012] The present inventors have found that a combination of a silica polymer and a light-emitting polymer substituted with a polar group is effective. It has been found that it is possible to provide stable luminescent particles having favorable colloid forming properties.

[0013] Thus, in a first aspect of the present invention, a silica polymer is provided, which comprises a main chain and pendants therefrom. and a light emitting polymer that includes pendant polar groups.

[0014] In a second aspect, the present invention provides a method for preparing a composition comprising the steps of: The present invention provides a colloidal suspension comprising:

[0015] In a third aspect, the present invention provides a method for producing a light-emitting photoluminescent device comprising the steps of: (a) polymerizing a silica monomer in the presence of a light-emitting polymer; The present invention provides a method for preparing a composite particle according to a first aspect of the present invention, comprising forming a silica polymer comprising: do.

[0016] The present inventors have investigated the colloidal stability of silica-containing particles, particularly in aqueous salt solutions. It has been found that this can be enhanced by providing polyether groups on the surface of the particles. .

[0017] Thus, in a fourth aspect, the present invention provides a silica having polyether groups on its surface. The present invention provides a particle comprising:

[0018] In a fifth aspect, the present invention provides a colloid comprising a liquid and a particle according to the fourth aspect. The body is preferably a protic liquid, which may be water or alcohol. or may have multiple salts dissolved therein. The liquid may be a buffer.

[0019] In a sixth aspect, the present invention provides a method of forming a particle according to the fourth aspect, comprising the steps of: The reactive group of the compound containing a polyether group is reacted with the particle to form the polyether group on the particle surface. covalently attaching to

[0020] The reaction at the surface of the particle can be between reactive groups on the surface and the silica, or between the silica and the reactive groups on the surface. The reaction may be between another reactive group on the surface of the compound (which may be an amine) and the reactive group of the compound. good.

[0021] The particles of the fourth embodiment may comprise or consist of silica.

[0022] The particles of the fourth embodiment may comprise silica and at least one luminescent material. The emissive material may be covalently attached to the particle or may be polymeric or non-polymeric. The particle may be a composite particle according to the first aspect.

[0023] The invention will now be explained in more detail with reference to the drawings. [Brief description of the drawings]

[0024] [Figure 1] FIG. 1 is a graph of average percent versus diameter (nm) for blue-emitting silica-LEP nanoparticles according to an embodiment of the present invention. [Diagram 2] FIG. 2 shows the absorption spectrum of blue-emitting silica-LEP nanoparticles according to an embodiment of the present invention. [Diagram 3] FIG. 3 shows a photoluminescence spectrum of blue-emitting silica-LEP nanoparticles according to an embodiment of the present invention. [Figure 4]FIG. 4 is a graph of the particle size distribution of colloidal suspensions in methanol of composite particles that have not been surface-treated and of composite particles that have been treated to form amino groups on their surfaces. [Diagram 5] FIG. 5 is a graph of the particle size distribution of colloidal suspensions in water of composite particles that have not been surface-treated and of composite particles that have been treated to form amino groups on their surfaces. [Figure 6] FIG. 6 is a graph of the particle size distribution of colloidal suspensions in phosphate buffered saline (pH 7.4) of composite particles that have not been surface-treated and of composite particles that have been treated to form polyethylene glycol chains on their surfaces. [Figure 7] FIG. 7 shows a UV absorption spectrum of green-emitting composite nanoparticles according to one embodiment. [Figure 8] FIG. 8 shows a photoluminescence spectrum of green-emitting composite nanoparticles according to one embodiment. [Figure 9] FIG. 9 is a graph of Z-average diameter versus light-emitting polymer concentration for green-emitting composite nanoparticles according to one embodiment. [Figure 10] FIG. 10 is a graph of Z-average diameter versus elementary volume for green-emitting composite nanoparticles according to one embodiment. [Figure 11] 11 is a graph of Z-average diameter versus silicate volume for green-emitting composite nanoparticles according to one embodiment; and [Figure 12] FIG. 12 is a graph of Z-average diameter versus total dilution ratio for green-emitting composite nanoparticles according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] In a first aspect of the present invention, a silica polymer is provided having a backbone and polar groups pendant thereto. The present invention provides a composite particle comprising a mixture of a light emitting polymer comprising:

[0026] As used herein, "silica polymer" means a polymer containing siloxane groups. Silica polymers are linear, branched, or polymeric polymers that contain or consist of alternating Si and O atoms. It may have a chain or a crosslinked backbone.

[0027] The silica polymer can form a matrix in which the light-emitting polymer is dispersed. The luminescent polymer and the silica polymer in the composite are not covalently bonded to each other. In order to form such covalent bonds during the formation of the molecule, the silica polymer and / or the luminescent The polymer does not need to be substituted with reactive groups.

[0028] Light emitting polymers may emit fluorescence, phosphorescence, or a combination thereof.

[0029] The light-emitting polymer may be a homopolymer or may be a polymer having two or more different repeat units. It may also be a copolymer comprising:

[0030] Light-emitting polymers can be made by incorporating poly(phenylene ether) groups pendant from or as end groups on the polymer backbone. In the case of phosphorescent polymers, phosphorescent metal complexes, preferably The phosphorescent iridium complexes are either pendant or attached to the polymer backbone. It may be provided as an end group of the polymer backbone.

[0031] The light-emitting polymer may have a non-conjugated main chain or may be a conjugated polymer. A "conjugated polymer" is a polymer that has repeat units in the polymer backbone that are directly conjugated to adjacent repeat units. A conjugated light-emitting polymer refers to a polymer that contains units that are bonded together along the polymer backbone. Polymers containing one or more arylene, heteroarylene and vinylene groups conjugated to Examples of suitable endothelial cell membranes include, but are not limited to, those described above.

[0032] Light emitting polymers can have linear, branched or crosslinked backbones.

[0033] The light-emitting polymer comprises one or more repeat units substituted with at least one polar group. The polar group or groups may be the only substituents of the repeat unit. or the repeat unit may comprise one or more non-polar groups (one or more C 1-40 The alkyl group may be further substituted with one or more alkyl groups, which may be hydrocarbyl groups. The repeat unit or units substituted with a polar group are the only repeat units of the polymer. or the polymer may be such that the or each repeat unit is a non-substituted or multiple non-polar groups (one or more C 1-40 Hydrocarbyl group The repeat unit may include one or more further co-repeat units which are substituted with (optionally)

[0034] C as described herein 1-40 The hydrocarbyl group is preferably C 1-20 Alkyl, unsubstituted Phenyl and one or more C 1-20 Phenyl substituted with an alkyl group. But not limited to these.

[0035] As used herein, a "polar group" is a group that is at least 0.0005 mg in an alcoholic solvent. / ml, preferably at least 0.001, 0.01, 0.1, 1, 5 or 10 mg / ml Another group that provides the light-emitting polymer with a solubility of 25 ml. The viscosity is measured at 100° C. Preferably, the alcohol solvent is 1-10 Alcohol, more preferred Methanol is preferred.

[0036] The polar group is preferably a group capable of forming hydrogen bonds or an ionic group.

[0037] In one embodiment of the first aspect of the invention, the light emitting polymer has the formula -O(R 3 O) q -R 4 (formula Medium, R 3 In each occurrence, C 1-10 is an alkylene group, C 1-5 Alkylene group, wherein one or more non-adjacent non-terminal C atoms of said alkylene group are O and R 4 is H or C 1-5 alkyl, and q is at least 1. and q is at least 2. More preferably, q is 2 to 5. The value of q is a group represented by the formula -O(R 3 O) q -R 4 All of The value of q may be different between polar groups of the same polymer. Good too.

[0038] R 3 As used herein with respect to 1-5 An "alkylene group" is a group represented by the formula -(CH2) f - (wherein f is 1 to 5).

[0039] Preferably, the light emitting polymer has the formula -O(CH2CH2O) q R 4 (wherein q is at least R is 1 and may be 1 to 10; 4 is C 1-5 Alkyl groups, preferably methyl. Preferably, q is at least 2. More preferably, q is 2 to 5, and most preferably q is 3.

[0040] In one embodiment of the first aspect of the present invention, the light emitting polymer has the formula -N(R 5 )2(in the formula, R 5 is H or C 1-12 Preferably, each R 5 is C 1-12 It is a hydrocarbyl.

[0041] In one embodiment of the first aspect of the invention, the light emitting polymer is anionic, cationic or The ionic group may be zwitterionic. It is a nonionic group.

[0042] Exemplary anionic groups are -COO - , sulfonic acid, hydroxide, sulfate, phosphate, phos It is a finic acid or phosphonic acid group.

[0043] Exemplary cationic groups are -N(R 5 )3 + (In the formula, each R 5 In each occurrence, H or C 1-12 Preferably, each R 5 is C 1-12 Hydrocal It's a building.

[0044] Light-emitting polymers containing cationic or anionic groups have the advantage that the charge of these ionic groups is A counter ion is included for balance.

[0045] The anionic or cationic group and the counterion can have the same valency, and the counterion The cation balances the charge of each anionic or cationic group.

[0046] The anionic or cationic groups may be monovalent or polyvalent. The ionic and cationic groups are monovalent.

[0047] The light-emitting polymer may include a plurality of anionic or cationic polar groups, The charges of two or more anionic or cationic groups are balanced by a single counterion. The polar groups are anionic or cationic groups with divalent or trivalent counterions. may include:

[0048] The counter ion may be a cation or a metal cation, Li + , Na + , K + , Cs + and preferably Cs + or an organic cation, Ammonium, such as tetraalkylammonium, ethylmethylimidazolium or It may also be pyridinium.

[0049] The counterion may be an anion, such as a halide; a sulfonate group (mesylate or trimethylol). silyl groups); hydroxides; carboxylic acids, sulfuric acids, phosphoric acids, phosphinic acids, phosphinic acids, It may also be a sulfonic or boronic acid group.

[0050] In one embodiment of the first aspect of the present invention, the light emitting polymer has the formula -O(R 3 O) q -R 4 of group, formula -N(R 5 )2 groups of the formula OR 4 and / or ionic groups Preferably, the light emitting polymer comprises a group of the formula -O(CH2CH2O) q R 4 A group of the formula -N (R 5 )2 groups and / or groups of the formula -COO -The anionic groups include a polar group selected from the group consisting of Preferably, the polar group is of the formula -O(R 3 O) q -R 4 a group of the formula -N(R 5 )2 base, and / or ionic groups. Preferably, the polar groups are selected from the group consisting of the formula -O(C H2CH2O) q R 4 a polyethylene glycol (PEG) group of the formula -N(R 5 )2 groups, and / or formula -COO - R 3 , R 4 , R 5 , and q are as described for other embodiments of the present invention.

[0051] The backbone of the light-emitting polymer may be a conjugated polymer. The backbone of the conjugated light-emitting polymer may be represented by the formula (I ) repeat units: [ka]

[0052] (In the formula, Ar 1 is an arylene group or a heteroarylene group, and Sp is a spacer group. m is 0 or 1, and independently in each occurrence, R 1 is a polar group, m is 0 If m is 1, then n is at least 1 and may be 1, 2, 3 or may be 4, R 2 is, independently in each occurrence, a nonpolar group; p is 0 or is a positive integer, q is at least 1 and may be 1, 2, 3 or 4, Sp, R 1 and R 2 may be independently the same or different in each occurrence).

[0053] Preferably, m is 1, and n is 2 to 4, more preferably 4. Preferably, p is 0. It is.

[0054] Ar in formula (I) 1 is C 6-20 An arylene group or a 5- to 20-membered heteroarylene group. Ar 1 is preferably C 6-20 Arylene groups include phenylene, fluoro, be it fluorene, benzofluorene, phenanthrene, naphthalene or anthracene Preferably, fluorene or phenylene is more preferred, and most preferably fluorene. Good too.

[0055] Sp-(R 1 )n may be a branched group and is a polar group (-NH2 or -OH group). The dendritic group may be substituted with, for example, polyethyleneimine.

[0056] Preferably, Sp is selected from: - one or more non-adjacent C atoms may be replaced by O, S, N or C=O C 1-20 Alkylene or phenylene-C 1-20 Alkylene; - one or more substituents R 1 In addition, it may be unsubstituted or may contain one or more non- Polar substituents (one or more C 1-20 may be substituted with an alkyl group) Good C 6-20 Arylene or 5- to 20-membered heteroarylene, more preferably phenylene hmm.

[0057] As used herein, "alkylene" refers to a divalent alkyl chain, branched or straight. .

[0058] As used herein, a "non-terminal C atom" of an alkyl group refers to the terminal methyl atom of an n-alkyl group. This refers to a C atom other than a methyl group at the end of an alkyl group or a branched alkyl chain.

[0059] More preferably, Sp is selected from: -C in which one or more non-adjacent C atoms may be replaced by O, S or CO 1- 20 alkylene; and - C, which may be unsubstituted or substituted with one or more non-polar substituents 6-20 Arylene or 5- to 20-membered heteroarylene, more preferably phenylene.

[0060] R 1 may be a polar group as described elsewhere herein. Preferably, R 1 Yes This is the following: -Formula -O(CH2CH2O) q R 4 A polyethylene glycol (PEG) group of formula (wherein q is at least 1 and may be 1 to 10; R 4 is C 1-5 Alkyl groups, preferably is methyl); -Formula-N(R 5 )2(wherein, R 5 is H or C 1-12 hydrocarbyl) groups; or -Formula-COO - Anionic groups.

[0061] When n is at least 2, each R 1 are independent in each occurrence and may be the same or different. Preferably, each R bonded to a given Sp group 1 is different.

[0062] When p is a positive integer and may be 1, 2, 3 or 4, the group R 2 Choose from the following: You can choose: -Alkyl(C 1-20 (which may be alkyl); and - aryl, which may be unsubstituted or substituted by one or more substituents; and heteroaryl groups, preferably one or more C 1-20 Substituted with an alkyl group Phenyl; - an optionally substituted straight or branched chain aryl or aryl group, each of which is independently Heteroaryl groups, such as those of the formula -(Ar 3 ) s wherein each Ar 3 are independently aryl or is a heteroaryl group and s is at least 2), preferably each group is unsubstituted. or one or more C 1-20 A branched chain optionally substituted with alkyl chain or straight chain phenyl groups; and - Crosslinkable groups, such as vinyl or acrylate groups, or benzocyclobutane groups A group containing a double bond.

[0063] Preferably, each R 2 If present, independently C 1-40 Selected from hydrocarbyl More preferably, C 1-20 Alkyl; unsubstituted phenyl; one or more C 1-20 a phenyl substituted with alkyl groups; and phenyl which is unsubstituted but substituted with one or more substituents. The aryl group is selected from optionally substituted, straight or branched chain phenyl groups.

[0064] The polymers described herein may contain only one form of repeat unit of formula (I) or may contain only one form of repeat unit of formula (I). It may consist of or contain two or more different repeat units of formula (I) , or may consist of it.

[0065] A polymer comprising one or more repeat units of formula (I) may comprise one or more co-repeat units It may also be a copolymer containing the units.

[0066] When co-repeat units are present, the repeat units of formula (I) are 0.1 to 99 mol %, 50 to 99 mol %, or 80 to 99 mol % of the Preferably, the repeat unit of formula (I) is at least one of the repeat units of the polymer. At least 50 mole %, more preferably at least 60, 70, 80, 90, 95, 98 or 9 Most preferably, the repeating units of the polymer are one or more of the formula (I): It consists of multiple repeating units.

[0067] The or each repeat unit of the polymer is selected to produce the desired emission color of the polymer. You can choose to do so.

[0068] The blue light-emitting polymer of the composite particles described herein has a wavelength of 500 nm or less, preferably 400 nm or less. Photoluminescence having a peak in the range of 400 to 490 nm The optical properties of the optical fiber may be determined by the optical properties of the optical fiber.

[0069] The green light-emitting polymer of the composite particles described herein has an emission wavelength of more than 500 nm up to 580 nm. Photoluminescence having a peak (which may be greater than 500 nm and up to 540 nm) The spectrum may be different from that of the conventional optical fiber.

[0070] The red light emitting polymer of the composite particles described herein has an emission wavelength of 580 nm or less to 630 nm. (which may be from 585 nm to 625 nm) The spectrum may be different from that of the conventional optical fiber.

[0071] The photoluminescence spectra of the light-emitting polymers described herein were measured using Hamamat It can be measured in solution using the instrument C9920-02 supplied by su .

[0072] The backbone of the polymer containing units of formula (I) may be non-conjugated or conjugated. stomach.

[0073] The polymers are preferably conjugated to each other and / or comprise repeat units of formula (I). The aromatic or heteroaromatic group of the adjacent repeat unit of formula (I) Exemplary conjugated polymers include arylene repeat units. Vinylene repeat unit;Arylene repeat unit;Heteroarylene repeat unit;Amin and combinations thereof.

[0074] If present, the or each co-repeat unit is unsubstituted or may be substituted with one or more non-polar substituents, and one or more repeat units is C 6-20 At least one selected from an arylene group and a 5- to 20-membered heteroarylene group. or may comprise or consist of a plurality of groups, said arylene group or heteroaryl group being Each loarylene group, at each occurrence, can be unsubstituted or one or more substituted aryl groups. The alkyl group may be substituted with one or more non-polar substituents.

[0075] The arylene repeat units of the polymer are fluorenes, preferably 2,7-linked fluorenes. phenylene, preferably 1,4-bonded phenylene; naphthalene, anthracene, indium Contains repeating units of denofluorene, phenanthrene and dihydrophenanthrene The arylene repeating unit is not limited to the above. The units can be selected from: [ka]

[0076] (In the formula, R 13 is independently, in each occurrence, a substituent; c is 0, 1, 2, 3 or is 4, preferably 1 or 2, and each d is independently 0, 1, 2 or 3, preferably 0 or 1, and e is 0, 1 or 2, preferably 2).

[0077] One or more unsubstituted or substituted 5- to 20-membered heteroarylenes in the polymer main chain Examples of repeating units that contain or consist of a thiophene repeating unit, a bis(2-phenylene) repeating unit, Examples of the repeating units include benzothiadiazole repeating units, benzothiadiazole repeating units, and combinations thereof. Exemplary heteroarylene repeat units include, but are not limited to, the following: Contains repeat units of VII), (VIII) and (IX): [ka]

[0078] (In the formula, R 13 is independently, at each occurrence, a substituent and f is 0, 1, or 2. (I).

[0079] R 13represents, independently in each occurrence, a polar group (polar substituent -(Sp) m -(R 1 ) n in (optionally present) or non-polar substituent R 2 may be a group comprising or consisting of Sp, m, R 1 and R 2 is as described for formula (I).

[0080] An arylene repeat unit or a heteroarylene repeat unit substituted with one or more polar groups. Repeat unit (formula -(Sp) m -(R 1 ) n The formula (III) to (III) IX) may be a repeat unit of formula (I).

[0081] Arylene that is unsubstituted or substituted only with one or more non-polar groups Repeating units or heteroarylene repeating units (repeat units of formulae (III) to (IX) unit) are co-repeat units of the polymer.

[0082] The amine repeat unit of the polymer may have the formula (XII): [ka]

[0083] (In the formula, Ar 8 , Ar 9 and Ar 10 is independently at each occurrence a substituted or non-substituted substituted aryl or heteroaryl; g is 0, 1 or 2, preferably 0 or 1, and R 13 is independently in each occurrence a substituent, and x, y and z are (each independently being 1, 2 or 3).

[0084] R 9 When g is 1 or 2, each occurrence may be the same or different, and preferably Preferably, it is alkyl, C 1-20 Ar may be alkyl; 11 and Ar 11 is selected from the group consisting of a branched or linear chain of Ar 11 independently in each occurrence, and n is substituted or unsubstituted aryl or heteroaryl.

[0085] Ar directly bonded to the same N atom 8 , Ar 9 , and Ar, if present 10 Oh And Ar 11 Any two aromatic or heteroaromatic groups selected from The linking atoms may be divalent linking atoms or groups. Preferred divalent linking atoms and groups include , O, S, substituted N and C.

[0086] Ar 8 and Ar 10 is preferably C 6-20 Aryl, more preferably phenyl. These may be unsubstituted or substituted with one or more substituents. stomach.

[0087] When g=0, Ar 9 is preferably C 6-20 Aryl, more preferably phenyl. These may be unsubstituted or substituted with one or more substituents. stomach.

[0088] For g=1, Ar 9 is preferably C 6-20 Aryl, more preferably phenyl or or a polycyclic aromatic group, such as naphthalene, perylene, anthracene or fluorene. They may be unsubstituted or substituted with one or more substituents.

[0089] R 9 is preferably Ar 11 or branched or linear Ar 11 It is a group. 11 is preferably phenyl at each occurrence, which may be unsubstituted or It may be substituted with one or more substituents.

[0090] Exemplary groups R 9 Examples of the aryl group include the following, each of which is unsubstituted: or substituted with one or more substituents, where * represents the point of attachment to N. vinegar: [ka]

[0091] (x, y and z are preferably each 1).

[0092] Ar 8 , Ar 9 , and, if present, Ar 10 and Ar 11 are each independently , unsubstituted or with one or more substituents (1, 2, 3 or 4 substituents) may be substituted with

[0093] The substituents are independently a polar group (polar substituent-(Sp) m -(R 1 ) n (It may be) or non-polar substituent R 2 and Sp, m, R 1 oh YobiR 2 is as described for formula (I).

[0094] Ar 8 , Ar 9 , and Ar, if present 10 and Ar 11 Preferred substituents for are , C 1-40 Hydrocarbyl, preferably C 1-20 It is an alkyl.

[0095] Preferred repeating units of formula (XII) are those of formulas (XII-1), (XII-2) and (XII-3). XII-3) containing unsubstituted or substituted units: [ka]

[0096] Preferably, the polymer comprising the repeat unit of formula (XII) comprises one or more aryl groups. The repeating unit (one or more arylene repeating units selected from the formulae (III) to (IX) 0.1 to 50 mol % of the light-emitting polymer further comprises a unit represented by the formula (X The repeat unit of the light-emitting polymer may be one or more repeat units of one or more repeat units of formula (XII) and one or more arylene repeat units (which may be one or more repeat units of formulae (III) to (IX)) , and may consist of it.

[0097] In the case of phosphorescent conjugated polymers, phosphorescent groups, preferably metal complexes, more preferably iridium complexes, are The iridium moiety may be provided as a polymer backbone, a side group and / or an end group. An exemplary conjugated repeat unit comprising a ruthenium complex has the formula: [ka]

[0098] Preferably, the repeat unit of formula (I) is a repeat unit of formula (Ia): [ka]

[0099] (Ia) (In the formula, R 2 , p, Sp, R 1 and n, independently in each occurrence, represents a repeat of formula (I). As described for repeating units.) Preferably, n is 2 in each occurrence. Preferably, p is 0 in each occurrence.

[0100] Exemplary repeat units of formula (Ia) are: [ka]

[0101] The silica polymer may include repeat units of formula IIa and / or IIb: [ka]

[0102] (In the formula, R 6 In each occurrence, H or C 1-12 Hydrocarbyl (H or C 1- 12 The silica polymer is independently selected from the group consisting of a silyl group having the formula (II) and a silyl group having the formula (II). It may further comprise a repeat unit of c): [ka]

[0103] The Si atom of the repeating unit of formula (II) is preferably an O atom in the polymer backbone or a repeating unit of formula OR6 Based on It will be understood that the aryl group is bound to

[0104] Preferably, at least 0.1% by weight of the total weight of the composite particle is made of the light-emitting polymer. Preferably, at least 1, 10, 25, or 50% by weight of the total weight of the composite particle is a luminescent polymer. It consists of mer.

[0105] Preferably, at least 50% by weight of the total weight of the composite particles is made up of silica polymer. Preferably, the total weight of the composite particles is at least 60, 70, 80, 90, 95, 98, 99, 99.5, 99.9% by weight is composed of silica polymer.

[0106] In one embodiment of the first aspect of the present invention, at least 70% by weight of the total weight of the composite particles is fused. Preferably, the composite particles are made of at least about 100% by weight of the total weight of the composite particles. 80, 90, 95, 98, 99, 99.5, 99.9% by weight of luminescent polymer and silica More preferably, the composite particle consists essentially of a luminescent polymer and a silica polymer. become.

[0107] In one embodiment of the first aspect of the invention, the composite particles are nanoparticles. Particles were measured using a Malvern Zetasizer Nano ZS at 5000n m or less, more preferably 2500 nm, 1000 nm, 900 nm, 800 nm, 700 nm, 600 nm, 500 nm or 400 nm or less. The nanoparticles were measured with a Malvern Zetasizer Nano ZS and had a mean particle size of 5-10 nm. The number average diameter may be 5000 nm, 10 to 1000 nm, preferably 25 to 60 0 nm, more preferably 50 to 500 nm, and most preferably 75 to 400 nm. The particle size includes particles having a diameter of 100 nm.

[0108] The composite particles may be provided as a colloidal suspension comprising the composite particles suspended in a liquid. Preferably, the liquid is water, 1-10 alcohols and mixtures thereof. Preferably, the colloidal suspension is free of surfactants.

[0109] The composite particles are fluorescent or phosphorescent. Preferably, the composite particles are fluorescent. The composite particle is for use as a fluorescent probe, more preferably a lateral Use as a fluorescent probe in immunoassays, such as flow or solid-state immunoassays The composite particles are intended for use in fluorescence microscopy or flow cytometry. It may also be for the purpose of

[0110] According to a third aspect of the present invention, the composite particle of any embodiment of the first aspect of the present invention is It can be formed by polymerization of silica monomers in the presence of a photopolymer.

[0111] In one embodiment, the method comprises treating a solution of silica monomer and a light-emitting polymer with a base. or adding a solution of silica monomer to a solution of light emitting polymer and base; The solvent of the solution is water, one or more C 1-10 Alcohol or a combination thereof do.

[0112] In another embodiment, the method comprises synthesizing the luminescent polymer in a solution of monomers under acidic conditions. The process involves polymerizing a monomer.

[0113] The mixture of silica polymer and luminescent polymer in the composite particles thus formed is homogeneous. One or more chains of a light-emitting polymer encapsulated within the particle, which may or may not be present; and / or Or, it may include, but is not limited to, one or more chains extending through the particle.

[0114] The polar groups of the luminescent polymer enhance the solubility of the polymer in polar solvents, and the absence of polar groups increases the solubility of the polymer in polar solvents. Compared to when the polymer is placed in a tight coil, the luminescent polymer is placed in a polar solvent. This prevents the formation of granules.

[0115] The composite particles were synthesized by a one-step method of polymerization of silica monomers in the presence of a light-emitting polymer. In some embodiments, the light-emitting layer may be formed from a light-emitting polymer and a silica monomer.

[0116] The silica monomer may be an alkoxysilane, preferably a trialkoxy or Tetraalkoxysilane, C 1-12 Trialkoxy or tetraalkoxysilane The silica monomer may be an alkoxysilane, for example, tetraethyl orthosilicate. It may be substituted only with a silyl group, or with one or more groups. In an embodiment, the silica monomer is substituted with a polyether group. The silica monomer reacts during polymerization of the silica monomer, as described in more detail below. The silica monomers are either free or substituted with reactive linking groups which are blocked during polymerization of the silica monomers.

[0117] The solution may comprise or consist of an ionic or protic solvent, preferably Preferably, the solvent comprises or is selected from water, alcohol and mixtures thereof. Exemplary alcohols include, but are not limited to, methanol, ethanol, 1- Propanol, isopropanol, 1-butanol, 2-butanol, t-butanol and and mixtures thereof. Preferably, the solution is methanol, ethanol, isopropyl alcohol, containing or containing an alcoholic solvent selected from propanol or mixtures thereof More preferably, the solution is selected from methanol, ethanol or a mixture thereof. Preferably, the solvent system is a non-alcoholic solvent other than water. No solvent.

[0118] In one embodiment of the third aspect of the invention, the base is an aqueous base, preferably a metal hydroxide. , preferably an alkali metal hydroxide, ammonium hydroxide or a tetraalkyl ammonium hydroxide. An aqueous solution of a hydroxide such as ammonium, preferably 10-40% w / w NH3 in water, preferably Or 20-30% w / w NH3 in water.

[0119] In one embodiment of the third aspect of the present invention, the weight ratio of the light emitting polymer:silica monomer is 1 :1 to 1:500, preferably 1:3 to 1:300, or 1:5 to 1:200, The most preferred ratio is 1:10 to 1:100. It was found that the particle diameter could be adjusted by selecting the ratio of the amounts.

[0120] In one embodiment of the third aspect of the invention, the concentration of the light emitting polymer in the solution is at least Each concentration is 0.0005 mg / ml, preferably at least 0.001, 0.01, 0.1, 1 Or 10 mg / ml.

[0121] A method of forming a composite particle may include the steps of: (a) one or more protic solvents, such as water, alcohols, and combinations thereof; (e.g., (b) adding a base to the solution obtained in step (a); and (c) adding a solution of silica monomer to the solution of step (b).

[0122] The method may be carried out in a homogeneous solution.

[0123] The composite particles are isolated after formation and resuspended in an aqueous solvent, an organic solvent, or a mixture thereof. The composite particles can be isolated from the reaction mixture by centrifugation.

[0124] The silica on the surface of the composite particle can be reacted to covalently bond the receptor to the silica surface. The receptor may be directly attached to the silica surface or may be spaced apart from the silica surface. This is also possible.

[0125] The chains that bind the receptor to the silica surface are capable of dissolving water or one or more solutes. Enhance the stability of colloids containing composite particles in protic liquids such as alcohols. The liquid may comprise or consist of a colloid stabilizing group.

[0126] In one embodiment, the receptor is covalently bound to the composite nanoparticles in a manner comprising the steps of: forming a first reactive group RG1 on a surface of silica; - a second reactive group capable of reacting with the first reactive group to form a covalent bond; reacting with a compound comprising a group RG2 and a third reactive group RG3; and - Reacting the third reactive group RG3 with the receptor to covalently attach the receptor to the composite nanoparticle. Process.

[0127] The silica on the surface of the composite particles is bonded to an organosilane (formula (X ) can be reacted with an organosilane of the formula: TIFF2024050748000012.tif27153 (in the formula, R 7 is H or a substituent, preferably C 1-10 is an alkyl group, Sp 1 is a spacer group, and RG1 is the first reactive group).

[0128] RG1 may be selected from the group consisting of: Amines, preferably -N(R 8 )2(wherein, R 8 is H or a substituent in each occurrence, preferably preferably H or C1-5 alkyl, more preferably H; Carboxylic acid or its ester (which may be an N-hydroxysuccinimide ester) stomach); alkene; alkyne; or SH; azide).

[0129] An exemplary organosilane is 3-aminopropyltriethoxysilane.

[0130] The reactive linking group BG1 is reacted with a compound of formula (XI): TIFF2024050748000013.tif29150 (wherein RG2 is a group capable of reacting with RG1 to form a covalent bond, and Sp2 is a spacer group and RG3 is a reactive linking group capable of binding to a receptor).

[0131] RG1 is an amine, and RG2 is a group capable of reacting with an amine (reacting with an amine It may be a group capable of forming an amide (which may be a carboxylic acid or an acid chloride). (a) may be used.

[0132] Sp1 and Sp2 may each be selected according to their colloid stabilizing properties.

[0133] The present inventors have found that the polyether chain spacer groups on the surface of the silica particles are particularly effective at a concentration of more than 10 mM. The colloids that make up the particles are stabilized in a buffer solution, such as an aqueous buffer solution having a salt concentration of I found that it is possible.

[0134] As used herein, a "polyether chain" refers to a bifunctional chain containing at least two ether groups. This means the valence chain.

[0135] Sp 1 and Sp2 each independently represent one or more non-adjacent C atoms being O, S, C (=O), C(=O)O, C(=O)NR 12 or NR 12 (Wherein, R12 represents each occurrence Independently, H and C1-12 hydrocarbyl (C1-12 alkyl may be a linear or branched divalent alkylene chain optionally substituted with The above may be selected from the above.

[0136] Preferably, at least one of Sp1 and Sp2 contains a repeat unit of formula (XI). Contains or consists of: TIFF2024050748000014.tif30153 (in the formula, R 14 and R 15 are each independently H or C 1-6 is alkyl, b is at least 1, may be 1 to 5, and is preferably 2; c is at least 2 and may be 2 to 1,000, preferably 10 to 500, 10 to 200 or The group of formula (XI) may be polydisperse. The group of formula (XI) may be at least It may have an Mn of at least 500 and may have an Mn of at least 2,000.

[0137] Preferably, Sp 1 and Sp 2 At least one of the groups contains a polyethylene glycol chain. or consisting of

[0138] Base Sp 1 and Sp 2 may have a chain length of 1 to 10 atoms, 1-10 It may have an alkylene chain, Sp 1 and Sp 2 The other is a repeating unit of formula (XI) Includes rank.

[0139] The binding group BG3 can be, but is not limited to, a biological material (peptide, carbohydrate, antibody, Genomes, enzymes, proteins, cell receptors, DNA, RNA, PNA, aptamers and natural products a composition; a biological material (which may be a recombinant antibody, an artificial protein); and biomimetics (synthetic receptors, biomimetic catalysts, combinatorial ligands) and an imprinted polymer) The preferred bioreceptor is streptavidin.

[0140] Without limitation, colloid-stabilizing groups and / or unprotected or protected groups polymerizing a silica monomer substituted with a reactive group RG1; and forming a composite particle having a formula (R 7 O )3Si-Sp 1 -RG3 (wherein Sp1 comprises a colloid stabilizing group) The receptor and / or colloid-stabilizing groups can be attached to the silica particles using other methods, including by It will be appreciated that the molecular weight can be covalently attached to the surface of the molecule.

[0141] In use, the particles having receptor groups on their surfaces bind to target biomolecules in a sample. Biomolecules include, but are not limited to, DNA, RNA, peptides, and carbon. Preferred biomolecules include hydrates, antibodies, antigens, enzymes, proteins and hormones. is biotin.

[0142] The sample is contacted with a composite nanoparticle as described herein, preferably a composite nanoparticle as described herein. The nanoparticles can be immobilized on the treated surface with a colloidal suspension containing the nanoparticles.

[0143] Gel permeation chromatography of the luminescent polymers or silica polymers described herein The number average molecular weight (Mn) measured in terms of polystyrene is approximately 1×10 3 ~1×10 8 , preferably 1 x 10 4 ~5×10 6 The polymers described herein may range from The weight average molecular weight (Mw) in terms of polystyrene is 1×10 3 ~1×10 8 , preferably 1x 10 4 ~1×10 7 It could be.

[0144] The polymers described herein are suitably amorphous polymers.

[0145] The composite particles described herein can be used in a variety of applications, including, but not limited to, biological imaging fluorescence microscopy. Can be used in microscopy, flow cytometry and fluorescence-based immunoassays can.

[0146] [Example 1] Preparation of blue-emitting silica-LEP composite nanoparticles by the Stober method: [ka]

[0147] No. 2012 / 133229, the contents of which are incorporated herein by reference. The disclosed LEP1 was heated at 60° C. for 1 hour to obtain methanol (1 mg / m The solution was then cooled to room temperature. Add 0.15 mL of ammonium hydroxide (30% aqueous solution) to 2 mL of solution, followed by stirring at room temperature. Add tetraethyl orthosilicate (TEOS, 0.2 mL) and methanol (0 A solution of 14.5 mL of 1,2-dichlorophenyl ether was added quickly. Stirring was continued at room temperature for 1 hour, after which the solution was diluted with 14 The resulting silica-LEP nanoparticles were centrifuged at 1,000 rpm for 10 min to separate the excess unreacted silica-LEP nanoparticles. The reaction mixture was separated from the supernatant, which contained TEOS and ammonium hydroxide. The supernatant was decanted. The nanoparticles were then pelleted using gentle sonication for 2.5 min. The mixture was then redispersed in 1 mL of fresh methanol. The washing cycle was repeated two more times, consisting of redispersion in 2.5 mL of ethanol followed by 2. The plate was washed three times with 5 mL of deionized water. Nanoparticles were used for particle size measurement by dynamic light scattering using the HPLC System Nano ZS. The pellet was redispersed in 1.5 mL of deionized water.

[0148] The solid content (mass / volume of nanoparticles) of the as-prepared nanoparticle suspension was 14, Solid nanoparticles were isolated from 1 mL of dispersion by centrifugation at 1,000 rpm. and by centrifugation, decantation and redispersion (as above). After washing twice with methanol and drying the solid pellet overnight, the mass of the solid was determined using a microbalance. The measurements were taken.

[0149] The optical density of the as-prepared nanoparticle dispersions was measured using a Cary 5000 UV-vis-I R spectrometer was used to determine.

[0150] Hamamatsu C9920-02 PL quantum yield spectroscopy with integrating sphere accessory The photoluminescence quantum yield of nanoparticles in aqueous dispersions was determined using a spectrophotometer. [Table 1]

[0151] Size distribution, absorption and photoluminescence spectra of these composite particles is shown in Figures 1 to 3.

[0152] Their extremely high fluorescence brightness, stability in aqueous buffers and surface attachment to biomolecules For ease, the prepared silica-LEP nanoparticles can be used as fluorescent tracers or optical probes. These are particularly suitable for use as tags for extraction assays.

[0153] Amino modification of composite nanoparticles A 3 mL suspension of composite nanoparticles in methanol (number average diameter by dynamic light scattering = 165 nm (solid content: approximately 4 mg / mL) with 120 μL of (3-aminopropyl)triethoxysilane The suspension was stirred at room temperature for 1 hour. The suspension was centrifuged at 14,000 rpm for 2 minutes. After separation, the resulting silica-LEP nanoparticles were treated with excess unreacted (3-aminopropyl) tetrahydrofuran. The supernatant containing ethoxysilane was removed by decantation. Using gentle sonication, pellet the isolated nanoparticles in 3 mL of fresh methanol. The mixture was centrifuged, decanted and redispersed in methanol (3 mL). The washing cycle was repeated two more times, consisting of dispersing the sample in water and then redispersing the sample in 3 mL of methanol. To prepare samples for dynamic light scattering analysis, 100 μL of the suspension was centrifuged and the supernatant was Decant as above and reconstitute the isolated nanoparticles in 1 mL of either methanol or water. It became suspended.

[0154] PEGylation of amino-modified composite nanoparticles 1 mL of the amino-modified composite nanoparticle suspension in methanol formed in the above example was incubated for 2 min at 14 °C for 2 min. The nanoparticles were isolated by centrifugation at 1,000 rpm and decantation of the supernatant. α,ω-Bis{2-[(3-carboxy-1-oxopropyl)amino]ethyl}poly(ethylene glycol) Ethylene glycol (Mr=2000g / mol, 10mg), N-(3-aminopropyl )-N-ethylcarbodiimide (2.1 mg) and N-hydroxysuccinimide (2 Nanoparticles were prepared by gentle sonication using 1 mL of a solution of 0.5 mg of 10 ... The pellet was redispersed and the resulting suspension was stirred at room temperature for 1 hour. The resulting silica-LEP nanoparticles were centrifuged at 400 rpm for 2 min to remove excess unreacted PEG. The supernatant was removed by decantation and gently eluted with water. Using sonication, redisperse the isolated nanoparticle pellet in 1 mL of fresh methanol. The procedure consisted of centrifugation, decantation, and redispersion in methanol (1 mL). The wash cycle was repeated two more times. Before the final centrifugation and decantation, The suspension was aliquoted into four 250 μL portions and the resulting pellet was stored at -20 °C prior to use. Ta.

[0155] Conjugation of streptavidin to PEGylated composite nanoparticles One of the isolated PEGylated conjugated nanoparticle pellets in the above example was gently The cells were resuspended in 1 mL of phosphate-buffered saline (pH 7.4) by sonication, followed by 50 μL of streptavidin solution (1 mg / mL) in the same buffer was immediately added. The solution was stirred at room temperature for 1 hour, and then the Sep (pre-washed with 150 mL of phosphate-buffered saline) was added. A 4.5 cm high, 3 cm diameter column packed with hacryl S-300 HR separation medium was The column was eluted with the same buffer and 1.5 mL fractions were collected. The column fractions containing the highest concentration of nanoparticles (based on light intensity) were selected for subsequent bioassay. Selected for use in

[0156] Evaluation of colloidal stability of composite nanoparticles in various dispersants The following test was used to characterize the composition of bare and functionalized composite nanoparticles (with the same base) in various dispersants. The relative stability of the 100% glycerol (prepared from 100% glycerol) was determined after centrifugation and decantation. The isolated composite nanoparticles (approximately 0.4 mg) were sonicated in a bath sonicator for 5 minutes. Immediately before DLS analysis, the nanoparticle suspension was further The mixture was sonicated for 1 min at 37 °C and then sonicated using a Malvern Zetasizer Nano ZS. Table 2 shows the surface and bare solubility of various dispersions as determined by DLS. The polydispersity index (PdI) of the modified composite nanoparticles and the corresponding number-average particle size distributions are shown in Figs. Shows. [Table 2]

[0157] Glass microscope slides functionalized with self-assembled monolayers of (3-aminopropyl)silane 1 g of succinic anhydride and 1 g of trimethylamine in acetonitrile (50 mL). After immersion in a solution containing 0.3 mL of acetonitrile for 16 h, the mixture was washed with fresh acetonitrile (50 mL). After drying, the plates were stored in Grace-Biol for subsequent binding assays. abs Secure Seal imaging spacer was used to obtain carboxy-functionalized Four circular regions (diameter = 9 mm) were isolated by fixing onto the surface of a glass slide. Within each isolated region of the Imide (77.0 mg) and N-hydroxylsulfosuccinimide (33.0 mg) After standing at room temperature for 30 minutes, the solution was The isolated area was washed three times with water (80 μL). After removing the last wash, Two of these regions were filled with 80 μL of biotinylated uracil in phosphate-buffered saline (pH 7.4). Serum albumin (50 μg / mL) solution was added to the remaining two regions at 0.01 wt. Bovine serum albumin was dissolved in phosphate buffered saline (pH 7.4) containing 100% Tween-20. 80 μL of blocking buffer containing 3% by weight of ethanol was added. After 1 h at room temperature, the Remove the solution from the two areas containing the tinned bovine serum albumin solution and place them After an additional hour at room temperature, the solution was The samples were then removed from all areas and each was placed in a phosphorus bath containing 0.01% by weight Tween-20. The sections were washed three times with acid-buffered saline (pH 7.4).

[0158] Biotin-binding assay using streptavidin-modified composite nanoparticles The bovine serum albumin modified regions prepared in the above examples (two were biotinylated and two were (non-biotinylated), streptavidin-modified composite nanoparticles as described in the previous examples were used. After standing at room temperature for 1 hour, the solution was removed and 0 in 80 μL of phosphate-buffered saline (pH 7.4) containing 0.01% by weight Tween-20. The plates were washed three times and once with 80 μL of deionized water. After drying in air, the plates were The fluorescence intensity of each of the C regions was measured using a microscope-based spectrometer with a mercury lamp as the excitation source. (λex=365 nm) and a fiber optic spectrometer for detection was used. As shown in Figure X, the mean integrated fluorescence intensity of the two assays containing biotin was significantly higher than that of the non-biotin assay. The Si-LEP nanoparticles were found to be specific for streptavidin, which was higher than that of the tinned control region. This demonstrates that the IgG1A-binding domain was immobilized on the surface via -biotin interactions.

[0159] [Example 2] Green-emitting silica-LEP composite particles using LEP2 as the conjugated polymer, Example 1 was obtained according to the same procedure as Stober et al. [ka]

[0160] The UV absorption and photoluminescence spectra of these nanoparticles were These are shown in Figures 7 and 8, respectively.

[0161] The photoluminescence quantum yield (PLQY) of the silica-LEP2 composite nanoparticles is 46%. It was found to be the case.

[0162] The particles have the following dimensions: Z average -195.5nm Number average -137.0nm Intensity average -225.5nm The particles have a PDI of 0.131.

[0163] The size of the composite nanoparticles varies with the concentration of the conjugated polymer, as shown in Figures 9 to 12, respectively. , by varying the silicate volume, base volume and / or overall dilution. and the Z-average diameter is measured by dynamic light scattering.

[0164] Although the present invention has been described with respect to certain exemplary embodiments, the following claims are intended to Various modifications and variations of the features disclosed herein may be made without departing from the scope of the present invention. and / or combinations will be apparent to those skilled in the art.

Claims

1. A particle comprising silica and at least one luminescent material, the particle having polyether groups on a surface thereof.

2. The particle of claim 1, wherein the luminescent material is polymeric.

3. The particle of claim 1, wherein the luminescent material is non-polymeric.

4. A particle according to any one of claims 1 to 3, wherein the luminescent material is covalently bonded to the particle.

5. A particle according to any one of claims 1 to 3, wherein the luminescent material is not covalently bonded to the particle.

6. A colloid comprising a liquid and a particle described in any one of claims 1 to 5.

7. The colloid of claim 6, wherein the liquid is a protic liquid.

8. The colloid of claim 7, wherein the protic liquid is water or an alcohol.

9. A colloid according to any one of claims 6 to 8, comprising one or more dissolved salts.

10. The colloid of claim 9, wherein the liquid is a buffer solution.

11. A method for forming particles, comprising the steps of:

1. A method comprising reacting a reactive group of a compound comprising a reactive group and a polyether group with a particle comprising silica and at least one luminescent material to covalently bond said polyether group to a surface of said particle.

12. The method of claim 11, wherein the reaction at the surface of the particle is a reaction between the reactive group and silica at the surface of the particle.

13. The method of claim 11, wherein the reaction at the surface of the particle is a reaction between a non-silica reactive group on the surface of the silica and the reactive group on the compound.

14. The method of claim 13, wherein the non-silica reactive group is an amine.